Keanekaragaman Jenis Ikan Di Sungai Sentangau Kabupaten Bengkayang Provinsi Kalimantan Barat - Bernadus, Bernadus; Soetignya, Widadi Padmarsari; Kurniadi, Bambang; Panggabean, Grin Tommy (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2024)
Abstrack. The fishery potential of the Sentangau River is quite large, which is shown by the activities of the local community and people from outside looking for fish. This study aims to determine the composition of species, abundance of species, diversity index, uniformity, dominance index and determine the quality of water in the Sentangau River, Seluas District, Bengkayang Regency, West Kalimantan Province. The results of the study showed that there were 23 species of fish found in the Sentangau River from 10 families and a total of 281 individuals. Cyprinidae is the most caught type of fish in the Sentangau River. The species Osteochilus hasselti is the most numerous individuals found. The highest type abundance value was Osteochilus hasselti with an average value of 36.30%. The value of the diversity index in Sungai Sentangau is in the medium category at each station, the average value of the uniformity index is in the high or stable category in.Keywords : Dominance, Diversity, Uniformity, River